التحليل الائتماني ودوره في ترشيد عمليات الإقراض المصرفي بالتطبيق على المصرف الصناعي السوري - الدغيم عبد العزيز; الأمين ماهر; انجرو إيمان (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يعتبر الائتمان المصرفي فعالية مصرفية غاية في الأهمية, حيث إن العائد المتولد عنه يمثل المحور الرئيسي لإيرادات أي مصرف مهما تعددت وتنوعت مصادر الإيراد الأخرى, وبدونه يفقد المصرف وظيفته الرئيسية كوسيط مالي في الاقتصاد. ولكنه في ذات الوقت استثمار تحيط به المخاطر, بسبب القروض والتسهيلات المتعثرة. وقد أصبح موضوع " التحليل الائتماني " من الموضوعات الشاغلة للنشاط المصرفي وللعاملين فيه بشكل عام, وكذلك لطلبة الدراسات المالية والمصرفية بشكل خاص, وذلك باعتباره أداة هامة للوصول إلى دقة في اتخاذ القرارات الائتمانية وبالتالي تخفيض الخسائر التي قد تتعرض لها المصارف. وانطلاقاً من أهمية الموضوع فقد تناولنا بالدراسة عملية منح الائتمان والدراسة التي تُُجرى على طلبات التسهيلات الائتمانية في المصرف الصناعي مقارنةً مع الركائز الأساسية للتحليل الائتماني, وذلك للتعرف على الجوانب الإيجابية وتعزيزيها, وكذلك على جوانب القصور وتقديم المقترحات والتوصيات للعمل على تلافيها وبما يسهم في ترشيد عمليات الإقراض المصرفي. Credit is considered the most important banking efficiency in that its generated returns represent the main axis of any bank returns, regardless of the multiplicity and variety of other returns sources; without credit, the bank loses its main function as a financial mediator in the economy. But at the same time, it is an investment fraught with many risks due to loaning and unsuccessful facilitations. The issue of ’’Credit analysis’’ has generally become of interest to the banking activity and its workers, specifically to the students of banking and financial studies. Given that it is an effective tool for accuracy in making credit decisions, consequently reducing the losses that banks may encounter, we have handled the process of giving credit and the process being implemented in credit facilitation in the Industrial Bank compared with the main bases of Creditory analysis; the purpose of this is to know and enhance the positive sides, and highlight the shortcomings and offer suggestions and recommendations for avoiding them in such away that contributes to guiding the processes of crediting..